Efektivitas Online Library Services di Era New Normal: Studi Pada UPT Perpustakaan Universitas Lampung - Purnamayanti, Arnila; Windah, Andi; Putra, Purwanto; Sugiyanta, Sugiyanta (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
(Objectives) This research examines the Effectiveness of Online Library Services in the New Normal Era. As we all know, it has been almost two years since the world has experienced a COVID-19 pandemic.This also has an impact on library institutions, where the library is the parent of the School/University Institution itself. With these conditions, like it or not, libraries are also required to continue to provide excellent service even in the current state of the COVID-19 pandemic in order to continue to support an optimal learning process. The UPT Library of the University of Lampung is under the auspices of the University of Lampung, currently the UPT of the library is trying to adapt to the